2016
DOI: 10.5114/aoms.2015.52030
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of chronic hepatitis D virus infection in Eastern Turkey: urbanization of the disease

Abstract: IntroductionBoth hepatitis B virus (HBV) and hepatitis D virus (HDV) infection play an increasingly important role in liver diseases. The main objective of this study was to investigate the socio-epidemiological, laboratory and radiological aspects of both HBV and HDV infection near the Iranian border of Turkey.Material and methodsThe study included 3352 patients with HBV and HDV infection. Socioepidemiological, laboratory and radiological aspects of the study subjects were retrospectively examined. Comorbid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 19 publications
1
14
0
7
Order By: Relevance
“…thrombocytopaenia (45%), elevated INR (23%)) are alarming. Importantly, the frequency of cirrhosis and hepatic decompensations reported for patients included in the HDIN data base is consistent with previously published single‐centre experiences, which mainly described European HDV genotype 1‐infected patients and reported cirrhosis in 34‐56% of cases . Recently, this high probability of liver related complications was also confirmed in the Swiss HIV/HDV cohort .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…thrombocytopaenia (45%), elevated INR (23%)) are alarming. Importantly, the frequency of cirrhosis and hepatic decompensations reported for patients included in the HDIN data base is consistent with previously published single‐centre experiences, which mainly described European HDV genotype 1‐infected patients and reported cirrhosis in 34‐56% of cases . Recently, this high probability of liver related complications was also confirmed in the Swiss HIV/HDV cohort .…”
Section: Discussionsupporting
confidence: 88%
“…In line with previously studied cohorts of HBV mono-infected and HCV infected patients 25,26 our analysis confirmed that men are more often HDV infected than women. However, remarkable differences in 27,28 and reported cirrhosis in 34-56% of cases. [29][30][31][32][33] Recently, this high probability of liver related complications was also confirmed in the Swiss HIV/HDV cohort.…”
Section: Discussionmentioning
confidence: 94%
“…HBV and HCV prevalences are 4 and 1% respectively [ 8 ]. Hepatitis D represents another considerable hepatitis etiology with a prevalence of 5–27% [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies indicate that the rate of anti-HDV positivity is lower in the Far Eastern countries with high HBV endemicity and higher in the Mediterranean countries with moderate HBV endemicity (12). As in the world, HDV frequency also shows regional differences in Turkey ( Figure 2) (12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28). Higher rates were reported in the Eastern and Southeastern Anatolian regions.…”
Section: Discussionmentioning
confidence: 84%